1991
DOI: 10.1143/jjap.30.2343
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Lead Alkaline-Earth Zirconate at Microwave Frequencies

Abstract: Dielectric properties of alkaline-earth-substituted PbZrO3 ceramics up to microwave frequencies were investigated. Although there were no preferable characteristics in the Ba- or Sr-substituted system, the ceramics in a (PbCa)ZrO3 system showed not only high dielectric constants in the range of 100 to 118, but also high Q values of 1000 to 1150 and small temperature coefficients of resonant frequency of 0 to 30 ppm/ °C. The crystal structure of the Ca-substituted ceramics was also investigated by X-ray powder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…To obtain the desired f two or more compounds with opposite temperature coefficients are typically employed to form a solid solution or mixed phases for tuning f . [8][9][10] Recently, Wise et al 11) have reported that Ca 0:8 Sr 0:2 TiO 3 has a high " r (¼ 181), a high quality factor (Q Â f ¼ 6100 GHz), and a high positive temperature coefficient of resonant frequency ( f ¼ 991 ppm/ C). Li 0:5 Nd 0:5 TiO 3 was reported to have a high negative temperature coefficient of resonant frequency ( f ¼ À310 ppm/ C), a high dielectric constant, and a high quality factor (" r ¼ 80, Q Â f ¼ 2100 GHz).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the desired f two or more compounds with opposite temperature coefficients are typically employed to form a solid solution or mixed phases for tuning f . [8][9][10] Recently, Wise et al 11) have reported that Ca 0:8 Sr 0:2 TiO 3 has a high " r (¼ 181), a high quality factor (Q Â f ¼ 6100 GHz), and a high positive temperature coefficient of resonant frequency ( f ¼ 991 ppm/ C). Li 0:5 Nd 0:5 TiO 3 was reported to have a high negative temperature coefficient of resonant frequency ( f ¼ À310 ppm/ C), a high dielectric constant, and a high quality factor (" r ¼ 80, Q Â f ¼ 2100 GHz).…”
Section: Introductionmentioning
confidence: 99%
“…A high dielectric constant and a stable temperature characteristic have been reported in a few dielectric materials such as BaO-PbO(Bi 2 O 3 )-TiO 2 -Nd 2 O 3 , 1) (Pb,Ca)ZrO 3 , 2) and CaO-Li 2 O-Ln 2 O 3 -TiO 2 (Ln = Sm, Nd). 3,4) Ezaki et al 3,4) The CaTiO 3 -(Li 1=2 Ln 1=2 )TiO 3 (Ln = Sm, Nd)-based microwave dielectric compositions have been reported to have a high dielectric constant and a stable temperature characteristic.…”
Section: Introductionmentioning
confidence: 96%
“…The most frequently used method to tune τ f is to form solid solution using two materials with opposite temperature coefficients . [3][4][5][6] However, not all ceramics can be improved by this method since the possible incompatibility of ionic radius, ionic charge or crystal structure will bring undesired secondary phase and damage the Q f value much.…”
Section: Introductionmentioning
confidence: 99%